The Green Paradox in Open Economies - Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper explains how, in the context of incomplete coordination among all countries, unilateral policies that might at first sight seem pro-green could actually turn out to harm the global environment. The free-riding motives and the difficulty of reaching an effective international environmental agreement are reviewed. As a first step, the various channels that lead to carbon leakage in static models of open economies are identified, and some simulation results are reported. This is complemented by a review of the possibility of green paradox outcomes in dynamic open-economy models with an exhaustible resource exploited by far-sighted firms. It is shown that border tax adjustments can lead to a green paradox outcome. Directions for future research are suggested.
Keywords: Q54; Q42; Q30; 330; green paradox; climate change; carbon leakage